Educational interventions for students with autism - Mundy, Peter; Mastergeorge, Ann. (San Francisco, CA : Jossey-Bass, 2012)
'This important volume provides information from national authorities on topics related to deepening educators' understanding of the issues and best practices involved in education for autism. To best meet the practical needs of teachers, parents, and school administrators, the editors will provide integrative summaries throughout the book, with recommendations for classroom use. Topics covered include: autism and its impact on schools; a teacher's view of autism and the classroom; best practices and challenges of working with students with ASD in the classroom; working with high-functioning autism (HFA) in schools; successful community-school partnerships; and options for teacher training'--Provided by publisher.
Includes bibliographical references (p. 253-291) and index.
Keywords: Autistic children -- Education -- United States; Autistic youth -- Education -- United States; Learning disabled children -- Education -- United States